2022
DOI: 10.2472/jsms.71.417
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Materials Reinforcement using Mechanically Defibrillated Cellulose Nanofibers

Abstract: Cellulose nanofibers (CNFs) are highly crystalline, fibrous materials with a high aspect ratio of long cellulose molecules linked together with strong hydrogen bonds. These long cellulose molecules are incorporated into hemicellulose and lignin, the cell walls of higher plants. The modulus of elasticity of CNF remains constant between 200 °C and +200 °C. However, the linear coefficient of thermal expansion of cellulose fibers was 0.17 ppm/K, which is comparable to that of quartz glass. Further, CNFs have a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…CNF composited polymers have shown better mechanical performance compared to the base polymer, making them suitable for various industries 15) such as automotive 16) , packaging 17) , medical implant 18) , electronics [19][20][21] , building material 22) , and paper 23) . On the other hand, there are very few reports on composite materials with cellulose added to metal-based matrices, with only a few examples being the addition of CNF to sintered metal materials by Kurita et al 24) and Osada et al 25) Therefore, we have proposed and studied the fabrication of metal-based CNF composite films by a electrolytic composite plating method 26,27) . Further improvement of wear resistance due to the intervention of CNF is expected by compositing CNF into nickel (Ni) plated film which is widely used industrially for its superior corrosion, wear, and heat resistance.…”
mentioning
confidence: 99%
“…CNF composited polymers have shown better mechanical performance compared to the base polymer, making them suitable for various industries 15) such as automotive 16) , packaging 17) , medical implant 18) , electronics [19][20][21] , building material 22) , and paper 23) . On the other hand, there are very few reports on composite materials with cellulose added to metal-based matrices, with only a few examples being the addition of CNF to sintered metal materials by Kurita et al 24) and Osada et al 25) Therefore, we have proposed and studied the fabrication of metal-based CNF composite films by a electrolytic composite plating method 26,27) . Further improvement of wear resistance due to the intervention of CNF is expected by compositing CNF into nickel (Ni) plated film which is widely used industrially for its superior corrosion, wear, and heat resistance.…”
mentioning
confidence: 99%
“…However, very few studies have reported on composite materials with cellulose added to metal-based matrices. Recently, in 2022, Kurita et al reported a titanium (Ti) sintered material with the addition of cellulose nanofibers [ 18 ]. The material was strengthened by the formation of titanium carbide from carbonized cellulose nanofibers during the sintering process, and the Ti–cellulose nanofiber composite material with 3.25 mass% cellulose nanofibers achieved a tensile strength of over 700 MPa, twice that of pure titanium [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in 2022, Kurita et al reported a titanium (Ti) sintered material with the addition of cellulose nanofibers [ 18 ]. The material was strengthened by the formation of titanium carbide from carbonized cellulose nanofibers during the sintering process, and the Ti–cellulose nanofiber composite material with 3.25 mass% cellulose nanofibers achieved a tensile strength of over 700 MPa, twice that of pure titanium [ 18 ]. In 2023, Osada et al applied cellulose nanofibers as an additive to binder in metal powder injection molding of stainless steel, and they reported the effects of suppressing deformation during sintering and reducing the oxygen content of sintered material [ 19 ].…”
Section: Introductionmentioning
confidence: 99%